Mobile app engagement as a motivational experience - Sanchez, Giulia Alves (2022)
The general objective of the research was to identify the influence of convenience/time, interactivity, compatibility, effort/expectation, on mobile app engagement, as well as whether mobile app engagement influences with private label connections mediated by relationship/commitment based on in the structural model of Kim and Baek. In order to do that, a survey was developed using structural equation modeling based on PLS. The questionnaire was applied to 566 consumers in the northeast region of Brazil. As a result, it was found that the constructs of hypotheses H1 to H4 positively influence mobile application engagement. The findings also showed that the H5 is confirmed, which means the engagement of mobile applications has an indirect effect on the relationship commitment, such as the H6 hypothesis, which asserts that the engagement of mobile applications has an indirect effect on the connections of own brand. Finally, hypothesis H7 is also confirmed by inferring that relationship commitment is positively linked to private label connections and is mediated by mobile app engagement.